Multi-modal hate speech detection using machine learning - Shill, Ponkoj Chandra; Boishakhi, Fariha Tahosin (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.